Sedentary behavior, abdominal obesity and healthcare costs in Brazilian adults with cardiovascular diseases: a cross-sectional study - Norberto, Maria Carolina Castanho Saes [UNESP]; Araujo, Monique Yndawe Castanho [UNESP]; Ricardo, Suelen Jane [UNESP]; Rodrigues Junior, Charles [UNESP]; Guiça, Juziane Teixeira [UNESP]; Turi-Lynch, Bruna Camilo [UNESP]; Codogno, Jamile Sanches [UNESP] (My University, 2024)
BACKGROUND: Research on the economic burden of sedentary behavior and abdominal obesity on health expenses associated with cardiovascular diseases is scarce. OBJECTIVE: The objective of this study was to verify whether sedentary behavior, isolated and combined with abdominal obesity, influences the medication expenditure among adults with cardiovascular diseases. DESIGN AND SETTING: This cross-sectional study was conducted in the city of President Prudente, State of São Paulo, Brazil in 2018. METHODS: The study included adults with cardiovascular diseases, aged 30-65 years, who were treated by the Brazilian National Health Services. Sedentary behavior was assessed using a questionnaire. Abdominal obesity was defined by waist circumference. Medication expenditures were verified using the medical records of each patient. RESULTS: The study included a total of 307 adults. Individuals classified in the group with risk factor obesity combined (median [IQ] USD$ 29.39 [45.77]) or isolated (median [IQ] USD$ 27.17 [59.76]) to sedentary behavior had higher medication expenditures than those belonging to the non-obese with low sedentary behavior group (median [IQ] USD$ 13.51 [31.42]) (P = 0.01). The group with combined obesity and sedentary behavior was 2.4 (95%CI = 1.00; 5.79) times more likely to be hypertensive. CONCLUSION: Abdominal obesity was a determining factor for medication expenses, regardless of sedentary behavior, among adults with cardiovascular diseases.
Keywords: Adult patients; Brazil; Chronic disease; Fat body; Health care costs; Medicines; Public health; Sedentary behavior; Waist circumference